Simplified damage models for circular section reinforced concrete bridge columns. (15th August 2020) - Perdomo, Camilo; Monteiro, Ricardo
Highlights: Damage models for circular section RC cantilever columns are developed. Three different Engineering Demand Parameters are considered. Simplified relationships for implementation in large scale assessment are proposed. Damage models for the limit state of shear failure are also generated. Critical discussion on the applicability of proposed damage models is presented. Abstract: Damage models are fundamental elements within probabilistic frameworks, such as Performance-Based Earthquake Engineering (PBEE), for the seismic assessment of RC structures. For bridges, in specific, there are not many available experimental results for the characterization of damage in the RC columns hence the numerical counterpart acquires particular relevance. In this paper, via Monte Carlo simulation and comparison with complementary experimental results, a damage model consisting of a library of median and logarithmic dispersion values for curvature ductility, displacement ductility and drift, describing the probability of reaching a particular damage limit state are generated as a function of key parameters of circular RC bridge columns. Four damage limit states are considered: slight, moderate, extensive and complete. Simplified relationships based on the full datasets are proposed for easier implementation. The proposed damage models can be used for threshold identification and economic loss assessment in performance-based earthquake engineering of RC bridges.